Team Woosh Generator 2012 WSGC Collegiate Rocket Competition - Dolby, Devin; Ihrcke, James; Jackson, Brandon; Johnson, Eric; Pajunen, Kirsti (Proceedings of the Wisconsin Space Conference, 2012)
The objective of the 2012 Wisconsin Space Grant Consortium Collegiate Rocket competition was to design, build, and launch a single-stage high powered rocket that is capable of transmitting live video from a downward looking camera during its ascent. The rocket must reach a target altitude of 3000 ft and deploy a parachute(s) electronically for a successful recovery. Upon recovery, the rocket must be determined to be in a flyable condition to be considered a successful launch. Teams receive a launch score based on their combination of reaching the desired altitude and the quality of their video received.1 After running preliminary simulations, Team Woosh Generator decided to select a Cesaroni J357 motor with a 3.0-in airframe diameter. A BoosterVision video recorder, transmitter and receiver system was selected to complete the live video feed requirement. The camera will be located on the exterior of the rocket and will be protected from drag forces during flight from a shroud. Upon reaching apogee a drogue shot will deploy under which the rocket will descend until it reaches an altitude of 500 feet. A second chute will then deploy such that a slow descent speed is obtained for landing. Redundant flight altimeters will be utilized to ensure proper chute deployment. Included in this report are design details considered, anticipated performance, photos of the construction process, and flight results.Â 